PASAR SUSU DUNIA DAN POSISI INDONESIA (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2010)
In 2009, domestic freshmilk production is about 1.3 million litre per day or equivalent 56,000 tons. That amount only capable to cover about 25% of domestic demand. In the last 2010 freshmilk national production will be 1.41 million litre per day or equivalent 62,000 tons. In 2009, milk consumption per capita per year is 10.3 KG this level is lower than the other member of Asean countries. Three kind of milk product dominated domestic milk market, i.e. powder milk (39%), sweetened condensed milk (35%), pasteurized milk (26%). For increasing domestic milk production, the goverment is necessary to deliver the incentive policy for the dairy farmers. It is necessary to empower the partnership scheme based on common interest between dairy farmers, dairy cooperative and milk processing industry. It is necessary to optimize the performance of external parties that related on milk agribusiness system, i.e. Union of Dairy Cooperative (GKSI), National Dairy Board (DPN), University and NGO. That extenal parties could collectively work to improve bargaining position, economic of scale and economic of scope af all dairy cooperatives in Indonesia. (JIIPB 2010 Vol 20 No 1: 65-76).   Keywords : freshmilk, milk processing industry, dairy cooperative, milk production, milk consumption, milk trade